Analisis Transportasi Siswa Menuju Sekolah dan Arahan Pengembangannya di Kota Bogor - Egi Syahril Mulia Purnama; Santun R.P. Sitorus; Janthy T Hidayat (Diponegoro University, 2020)
School is one system activities that generates movement and will attract movement from settlements as student residence. The objectives of this research are, to analyze the attraction of school students, to analyze the factors that influence the selection of public transport modes towards schools, analyzing the selection of student public transport modes and to formulate the direction for effective plan for developing school transportation in Bogor City. The methods used are flow mapping method, binary logistic regression method, proximity analysis, and descriptive analysis. The results show that the attraction of elementary students is sufficiently appropriate because they followed the zoning regulation which can be seen from the majority of students come from designated zone, while the result of junior high school student’s attraction show relatively insufficient because the majority of the students come from outside the designated zones. The estimation results of factors that significantly influence the choice of modes of transportation are gender, school distance, travel time, costs, consideration of costs, consideration of walking, and consideration of time. Half of elementary school students use angkot by 51% and 49% others students used other modes towards school. Most junior high school students also use angkot by 73% and 27% others students used other modes. The direction of school transportation development is focused on implementing a zoning system that is maximally implemented so that the movement of students to school is more organized and deviding of school clusters so that the school bus service will run effectively.